Mediatization of Religion in the Digital Era: A Case Study of Habib Ja'far's "Login" Podcast in Religious, Media, and Community Relations - Irfan Haniful Qoyyim; Muhammad Fahmi Syihab (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study explores the phenomenon of religious mediatization in the digital era through a case study of the “Login” podcast hosted by Habib Ja’far. The research focuses on how religious practices, clerical authority, and spiritual meanings are transformed through interaction with digital media logic. Employing a qualitative approach with discourse analysis and content observation, the study examines adaptive communication strategies in digital da’wah addressing younger audiences. Findings reveal that Habib Ja’far successfully constructs an inclusive dialogical space where religion emerges as an open, light, and contextually relevant narrative. In this sense, religious mediatization goes beyond message dissemination, becoming a negotiation of identity and authority within the digital public sphere.